Low-hydrogen-permeation polyolefin composite material as well as preparation method and application thereof
By blending modified petroleum resin with ultra-high molecular weight polyethylene, mixing it with high-density polyethylene, adding nucleating agent and compatibility agent, mechanical mixing and vulcanizing machine pressing treatment, the low crystallization efficiency of UHMWPE/HDPE composite materials is solved and the low crystallization efficiency and The problem of high hydrogen permeability has achieved high mechanical properties and low hydrogen permeability of polyolefin composite materials.
Patent Information
- Application Number
- CN202411460189.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing UHMWPE/HDPE composite materials have problems such as low crystallization efficiency, poor crystallinity and high hydrogen permeability of sheets.
Modified petroleum resin is prepared by mixing petroleum resin with xylene, oxidation reaction and hydrothermal reaction, and then blending it with ultra-high molecular weight polyethylene, cooling it with high-density polyethylene, adding nucleating agent and compatible The agent is mechanically mixed, and finally a low-hydrogen permeable polyolefin composite material is produced by a flat vulcanizer press plate.
The tensile strength, elongation of break and modulus of polyolefin composite materials are improved, while significantly reducing hydrogen permeability and enhancing hydrogen storage effect.
Smart Images

Figure CN119410047A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sheet material preparation, and in particular relates to a low hydrogen permeability polyolefin composite material and a preparation method and application thereof. Background Art
[0002] Hydrogen is a renewable, clean energy carrier that can store or transport large amounts of energy. In order to realize a hydrogen energy system in the near future, appropriate hydrogen storage and transportation technologies must be established. At present, gaseous hydrogen storage, liquid hydrogen storage, and solid hydrogen storage systems are all hydrogen storage tanks. However, in the face of heavy and costly metal hydrides, non-metallic tanks have the advantages of light weight, strong designability, and high toughness, while also reducing carbon emissions. Among them, the more typical non-metallic tank is made of polyolefin material. With the maturity of polyolefin large-scale production technology and the reduction of its production cost, the application of polyolefins in packaging, containers, pipelines and other fields has attracted widespread attention in recent years. However, polyolefin composite materials are prone to aging and low crystallinity.
[0003] Ultra-high molecular weight polyethylene (UHMWPE) is an excellent engineering plastic with high strength and wear resistance, good chemical stability and fatigue resistance, low friction and excellent biocompatibility, which makes UHMWPE have broad application prospects in engineering bearings, valves, automotive parts and biomedical implants. Although the long chain gives UHMWPE extremely high performance, its severe entanglement and the resulting extremely high melt viscosity also bring great difficulties to the processing of UHMWPE. In addition, high-density polyethylene (HDPE) is widely used in the industrial field due to its excellent physical properties and excellent mechanical properties. As a semi-crystalline polymer, the overall performance of HDPE is severely restricted by crystallinity, crystallization rate, etc.
[0004] There are many public reports on the preparation of UHMWPE / HDPE composite materials. CN109333897A discloses a dense skew-crystallized ultra-strong and ultra-wear-resistant polyethylene composite material and its preparation method. High-density polyethylene and ultra-high molecular weight polyethylene are dried and mechanically mixed to obtain a premix, which is then melt-blended, granulated, and dried by an extruder to obtain a blend pellet. The obtained blend pellet is molded by superimposing an oscillation and a push-pull composite force field during the melt molding process to prepare a dense skew-crystallized ultra-strong and ultra-wear-resistant polyethylene composite material.
[0005] CN104004253A discloses a high molecular weight polymer nucleating agent modified ultra-high molecular weight polyethylene blend material, wherein the mass fractions of each component in 100 mass fractions of high molecular weight polymer are: UHMWPE 60-100 parts, HDPE 5-12 parts, LLDPE 6-16 parts, high molecular weight polymer nucleating agent 0.1-3 parts and flow modifier 1.5-3 parts; the mixing ratio is any ratio to obtain a UHMWPE / HDPE composite material with good tensile properties and good impact resistance; CN116874906A discloses a UHMWPE modified PE pipe special material, which uses HDPE as raw material, HDPE 60-85 parts, UHMWPE 5-30 parts, filler 5-10 parts, composite lubricant 0.2-1 parts, composite antioxidant 0.1-0.3 parts, coupling agent 0.3 -1 part, by adjusting the type of raw materials, raw material ratio and process parameters, the processing performance of the composite material is improved, and finally a special material for PE pipes with good heat resistance, pressure resistance and wear resistance is obtained; CN117024867A discloses a method for preparing HDPE / UHMWPE / YPnm alloy material, wherein the components of the composite material are: 15 to 20 parts of nano-modified plastic composite material, 70 to 80 parts of high-density polyethylene and 15 to 20 parts of ultra-high molecular weight polyethylene, to obtain a composite material with good mechanical properties and high strength.
[0006] Although the above known technologies can prepare UHMWPE / HDPE blended composite materials, there are still problems such as low crystallization efficiency, poor crystallinity, and high hydrogen permeability of the sheet. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a low hydrogen permeation polyolefin composite material.
[0010] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a low hydrogen permeability polyolefin composite material, comprising:
[0011] Mixing petroleum resin and xylene to prepare a xylene petroleum resin mixed solution;
[0012] An oxidant is added to a xylene petroleum resin mixed solution to carry out an oxidation reaction, and after cooling, the solution is hydrothermally reacted with monoethanolamine to obtain a modified petroleum resin;
[0013] The ultra-high molecular weight polyethylene and the modified petroleum resin are blended and melted, and then cooled to obtain an ultra-high molecular weight polyethylene modified composite material;
[0014] The high-density polyethylene and ultra-high molecular weight polyethylene modified composite materials are mixed, a nucleating agent and a compatibilizer are added, and then mechanically mixed to obtain polyolefin composite material particles;
[0015] The polyolefin composite material particles are passed through a flat plate vulcanizing machine to obtain a low hydrogen permeability polyolefin composite material.
[0016] As a preferred embodiment of the preparation method of the present invention, the petroleum resin is 9 to 13 parts and the xylene is 87 to 96 parts by weight of the raw materials.
[0017] As a preferred embodiment of the preparation method of the present invention, the oxidant is an oxygen-ozone mixture, wherein O 3 The volume concentration is 2%.
[0018] As a preferred embodiment of the preparation method of the present invention, the oxidation reaction has a reaction temperature of 3 to 8° C. and a reaction time of 20 to 50 min.
[0019] As a preferred embodiment of the preparation method of the present invention, the mass percentage of monoethanol and cooled xylene petroleum resin solution is 6-12%:88-94%; the hydrothermal reaction has a reaction temperature of 70-90°C and a reaction time of 1-3h.
[0020] As a preferred embodiment of the preparation method of the present invention, the ultra-high molecular weight polyethylene and the modified petroleum resin are blended and melted, wherein the weight average molecular weight of the ultra-high molecular weight polyethylene is 3 to 9 million, and the weight average molecular weight of the modified petroleum resin is 1000 to 2500; the blending and melting includes blending and melting in the mixing chamber of a Haake rheometer 300P, wherein the rotor speed is 50 to 70 rpm, the temperature is 150 to 170°C, and the time is 7 to 15 min.
[0021] As a preferred embodiment of the preparation method of the present invention, the ultra-high molecular weight polyethylene modified composite material is 10 to 50 parts by weight, the high-density polyethylene is 50 to 90 parts by weight, the content of the nucleating agent is 0.003 to 1 part by weight, and the content of the compatibilizer is 0.4 to 2 parts by weight.
[0022] The weight average molecular weight of the high-density polyethylene is 120,000 to 300,000.
[0023] As a preferred embodiment of the preparation method of the present invention, the mechanical mixing, wherein the conditions of the mixed extrusion include: a rotor speed of 2000 to 4500 rpm, a feed rate of 0.3 to 3 kg / h, and a barrel temperature of 200 to 250°C;
[0024] The platen vulcanizing press platen pressing conditions include: temperature of 180-220° C., pressure of 10-20 MPa, and time of 5-20 min.
[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide a low hydrogen permeability polyolefin composite material, wherein: the low hydrogen permeability polyolefin composite material has a tensile strength of 1.6 to 4.2 cN / dtex, an elongation at break of 30% to 62%, a modulus of 27 to 68 cN / dtex, and a hydrogen permeability of 1.56×10 -16 ~4.687×10 -16 mol / (m·s·Pa).
[0026] Another object of the present invention is to overcome the deficiencies in the prior art and provide a low hydrogen permeability polyolefin composite material for use in the preparation of a hydrogen storage container.
[0027] Beneficial effects of the present invention:
[0028] (1) In the preparation process of the low hydrogen permeability polyolefin composite material of the present invention, the petroleum resin is first modified by monoethanolamine, and then the ultra-high PE is modified by the modified petroleum resin, which can increase the fluidity of the ultra-high PE and improve the nucleation and crystallization ability of the ultra-high PE, which helps to further enhance the hydrogen storage effect of the polyolefin composite material.
[0029] (2) The low hydrogen permeability polyolefin composite material of the present invention is also filled with a composite material. The core material is composed of a nucleating agent (barium sulfate and calcium carbonate) and a compatibilizer (maleic anhydride), which helps to increase the crystallization rate and crystallinity of the polyolefin composite material. Maleic anhydride grafted polyolefin helps to increase the dispersion performance of the composite filler.
[0030] (3) In the preparation process of the low hydrogen permeability polyolefin composite material of the present invention, ultra-high PE and HDPE are modified by ultra-high speed screw blending and melt extrusion. Because the speed is much higher than that of the traditional screw, it is helpful to disperse the ultra-high PE and inorganic filler in HDPE, promote the crystallinity of the system, and further improve the mechanical properties and low hydrogen permeability performance of the polyolefin composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0032] Figure 1 1 is the viscoelastic diagram of the materials prepared in Examples 1 to 6 of the present invention.
[0033] Figure 2 1 is the viscoelastic diagram of the materials prepared in Examples 7 to 12 of the present invention.
[0034] Figure 3 The viscoelastic diagrams are of the materials prepared in Comparative Examples 1 to 5 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0038] In the present invention, unless otherwise specified, "UHMWPE" refers to high molecular weight polyethylene; "HDPE" refers to high density polyethylene; "PR" refers to petroleum resin; and "MEA" refers to monoethanolamine (2-hydroxyethylamine).
[0039] In the embodiments of the present invention, the molecular weight of petroleum resin is 300-3000, purchased from Puyang Zhongke Xinyuan Petrochemical Co., Ltd.; the molecular weight of monoethanolamine is 61.08, purchased from Nanjing Lexuan Chemical Co., Ltd.; the molecular weight of HDPE is 120,000-300,000, purchased from Dongguan Weicai Plastic Raw Materials Co., Ltd.
[0040] The method for measuring the tensile strength in the embodiment of the present invention is as follows:
[0041] The mechanical properties (including tensile strength, elongation at break, and modulus) were measured by a universal tensile testing machine (refer to the national standard GB / T 14344); the hydrogen permeability value was measured by a hydrogen permeability tester (refer to the national standard GB / T42610-2023).
[0042] Example 1
[0043] This embodiment provides a method for preparing a low hydrogen permeability polyolefin composite material, the main steps of which are:
[0044] (1) taking 13 parts by weight of petroleum resin and 87 parts by weight of xylene solvent to obtain a xylene petroleum resin mixed solution;
[0045] The xylene petroleum resin solution was added into the bubble reactor, and then the ozone-oxygen mixture (O 3 -2% volume concentration) at 0.07s -1 It was introduced into the reactor and reacted at 8°C for 50 minutes. After cooling, the xylene petroleum resin solution was mixed with monoethanolamine at a mass ratio of 94% and 6%, and then added into a glass reactor equipped with a reflux condenser and a stirring device, and reacted at 90°C for 2.5 hours. Modified petroleum resin was obtained.
[0046] (2) taking an ultra-high molecular weight polyethylene with a weight average molecular weight of 9 million and a modified petroleum resin with a weight average molecular weight of 2500, the above-mentioned composition is blended and melted in the mixing chamber of a Haake rheometer 300P, and then cooled to obtain an ultra-high molecular weight polyethylene modified composite material, with a rotor speed of 70 rpm, a temperature of 170° C., and a time of 15 min;
[0047] (3) HDPE is 60 parts by weight, and UHMWPE modified composite material is 40 parts by weight; based on 100 parts by weight of HDPE and UHMWPE, nucleating agents barium sulfate and calcium carbonate, and compatibilizer maleic anhydride are mechanically mixed in a ratio of 0.04 parts by weight, 0.06 parts by weight, and 1 part by weight, respectively, with a rotor speed of 4000 rpm, a feed rate of 0.5 kg / h, and a barrel temperature of 235°C;
[0048] The polyolefin composite material particles are pressed by a flat plate vulcanizing machine to obtain a polyolefin composite material sheet (length*width 1.8×12m, thickness 20-30mm) at a temperature of 190° C., a pressure of 12 MPa, and a time of 7 minutes.
[0049] The properties of the polyolefin composite sheet were tested, and the test results are shown in Table 1.
[0050] Example 2
[0051] This embodiment provides a method for preparing a low hydrogen permeability polyolefin composite material, which is based on the method of embodiment 1, except that:
[0052] In step (3): based on 100 parts by weight of the HDPE and UHMWPE modified composite material, the nucleating agent and the compatibilizer are mechanically mixed in a ratio of 0.2 parts by weight of barium sulfate, 0.3 parts by weight of calcium carbonate, and 1.2 parts by weight of maleic anhydride. The test results are shown in Table 1.
[0053] Example 3
[0054] This embodiment provides a method for preparing a low hydrogen permeability polyolefin composite material, the main steps of which are:
[0055] (1) 9 parts by weight of petroleum resin and 96 parts by weight of xylene solvent are taken to obtain a xylene petroleum resin mixed solution;
[0056] The xylene petroleum resin solution was added into the bubble reactor, and then the ozone-oxygen mixture (O 3 -2% volume concentration) at 0.03s -1 The mixture was introduced into a reactor and reacted at 3°C for 40 minutes; after cooling, the xylene petroleum resin solution was mixed with monoethanolamine at a mass ratio of 88% and 12%, and then added into a glass reactor equipped with a reflux condenser and a stirring device, and reacted at 70°C for 2 hours to obtain a modified petroleum resin;
[0057] (2) taking an ultra-high molecular weight polyethylene with a weight average molecular weight of 3 million and a modified petroleum resin with a weight average molecular weight of 1000, the above composition is blended and melted in the mixing chamber of a Haake rheometer 300P, and then cooled to obtain an ultra-high molecular weight polyethylene modified composite material, the rotor speed is 50 rpm, the temperature is 150° C., and the time is 7 min;
[0058] (3) 85 parts by weight of HDPE and 15 parts by weight of UHMWPE modified composite material;
[0059] Based on 100 parts by weight of HDPE and UHMWPE, the components of the nucleating agent and the compatibilizer were mechanically mixed at a ratio of 0.02 parts by weight of barium sulfate, 0.04 parts by weight of calcium carbonate and 0.8 parts by weight of maleic anhydride, respectively, with a rotor speed of 4000 rpm, a feed rate of 1 kg / h and a barrel temperature of 235°C;
[0060] The polyolefin composite material particles are pressed by a flat plate vulcanizing machine to obtain a polyolefin composite material sheet at a temperature of 180° C., a pressure of 10 MPa, and a time of 5 minutes.
[0061] The test results are shown in Table 1.
[0062] Example 4
[0063] This example prepares a low hydrogen permeability polyolefin composite material according to the method of Example 3, except that:
[0064] In step (3): based on 100 parts by weight of the HDPE and UHMWPE modified composite material, the nucleating agent and the compatibilizer are mechanically mixed in a ratio of 0.11 parts by weight of barium sulfate, 0.09 parts by weight of calcium carbonate and 1.1 parts by weight of maleic anhydride, respectively. The test results are shown in Table 1.
[0065] Example 5
[0066] This embodiment provides a method for preparing a low hydrogen permeability polyolefin composite material, the main steps of which are:
[0067] (1) taking 10 parts by weight of petroleum resin and 90 parts by weight of xylene solvent to obtain a xylene petroleum resin mixed solution;
[0068] The xylene petroleum resin solution was added into the bubble reactor, and then the ozone-oxygen mixture (O 3 -2% volume concentration) at 0.07s -1 The mixture was introduced into a reactor and reacted at 8°C for 50 minutes. After cooling, the xylene petroleum resin solution was mixed with monoethanolamine at a mass ratio of 94% and 6%, and then added into a glass reactor equipped with a reflux condenser and a stirring device, and reacted at 90°C for 2.5 hours to obtain a modified petroleum resin.
[0069] (2) taking an ultra-high molecular weight polyethylene with a weight average molecular weight of 6 million and a modified petroleum resin with a weight average molecular weight of 1800, the above composition is blended and melted in the mixing chamber of a Haake rheometer 300P, and then cooled to obtain an ultra-high molecular weight polyethylene modified composite material, the rotor speed is 60 rpm, the temperature is 160° C., and the time is 10 min;
[0070] (3) HDPE is 70 parts by weight, and UHMWPE modified composite material is 30 parts by weight; based on 100 parts by weight of HDPE and UHMWPE, the components of nucleating agent and compatibilizer are mechanically mixed at a ratio of 0.03 parts by weight of barium sulfate, 0.04 parts by weight of calcium carbonate and 1 part by weight of maleic anhydride, respectively, with a rotor speed of 3800 rpm, a feed rate of 0.5 kg / h, and a barrel temperature of 240°C;
[0071] The polyolefin composite material particles were subjected to a vulcanizing press to obtain a polyolefin composite material sheet at a temperature of 200° C., a pressure of 15 MPa, and a time of 10 min. The test results are shown in Table 1.
[0072] Example 6
[0073] This example prepares a low hydrogen permeability polyolefin composite material according to the method of Example 5, except that:
[0074] In step (3): based on 100 parts by weight of the HDPE and UHMWPE modified composite material, the nucleating agent and the compatibilizer are mechanically mixed in a ratio of 0.02 parts by weight of barium sulfate, 0.03 parts by weight of calcium carbonate and 0.5 parts by weight of maleic anhydride, respectively. The test results are shown in Table 1.
[0075] The viscoelastic diagrams of the materials obtained in Examples 1 to 6 are shown in Figure 1 As can be seen from the figure, the modulus of the sheet is very high by modifying the ultra-high PE with modified petroleum resin and the effect of the ultra-high speed screw, indicating a synergistic effect of promoting crystallization; at the same time, it can be seen from Examples 1-2 that nucleating agents and compatibilizers can also promote crystallization; Examples 3-4 show that the use of modified petroleum resin for modification can promote the crystallization of HDPE; and the comparison between Examples 5-6 and Examples 1-4 proves the promoting effect of the high speed of the ultra-high speed screw on its crystallization.
[0076] Example 7
[0077] This embodiment provides a method for preparing a low hydrogen permeability polyolefin composite material, the main steps of which are:
[0078] (1) 8 parts by weight of petroleum resin and 92 parts by weight of xylene solvent are taken to obtain a xylene petroleum resin mixed solution; the xylene petroleum resin solution is added to a bubble reactor, and then an ozone-oxygen mixture (O 3 -2% volume concentration) at 0.07s -1 The mixture was introduced into a reactor and reacted at 8°C for 50 minutes. After cooling, the xylene petroleum resin solution was mixed with monoethanolamine at a mass ratio of 94% and 6%, and then added into a glass reactor equipped with a reflux condenser and a stirring device, and reacted at 90°C for 2.5 hours to obtain a modified petroleum resin.
[0079] (2) An ultra-high molecular weight polyethylene with a weight average molecular weight of 1.5 million and a modified petroleum resin with a weight average molecular weight of 300 were blended and melted in the mixing chamber of a Haake rheometer 300P, and then cooled to obtain an ultra-high molecular weight polyethylene modified composite material. The rotor speed was 40 rpm, the temperature was 130°C, and the time was 5 min.
[0080] (3) 50 parts by weight of HDPE and 50 parts by weight of UHMWPE modified composite material;
[0081] Based on 100 parts by weight of HDPE and UHMWPE, the components of the nucleating agent and the compatibilizer were mechanically mixed at a ratio of 0.004 parts by weight of barium sulfate, 0.004 parts by weight of calcium carbonate and 0.4 parts by weight of maleic anhydride, respectively, with a rotor speed of 3000 rpm, a feed rate of 0.3 kg / h and a barrel temperature of 200°C;
[0082] The polyolefin composite material particles were subjected to a platen vulcanizing press to obtain a polyolefin composite material sheet at a temperature of 180° C., a pressure of 10 MPa, and a time of 5 min. The test results are shown in Table 1.
[0083] Example 8
[0084] This example prepares a polyolefin composite sheet according to the method of Example 7, except that:
[0085] In step (3): based on 100 parts by weight of the HDPE and UHMWPE modified composite material, the nucleating agent and the compatibilizer are mechanically mixed in a ratio of 0.4 parts by weight of barium sulfate, 0.6 parts by weight of calcium carbonate and 2 parts by weight of maleic anhydride, respectively; the rotor speed is 4000 rpm, the feed rate is 8 g / min, the barrel temperature is 230°C, and the test results are shown in Table 1.
[0086] Example 9
[0087] This embodiment provides a method for preparing a low hydrogen permeability polyolefin composite material, the main steps of which are:
[0088] (1) 15 parts by weight of petroleum resin and 85 parts by weight of xylene solvent are taken to obtain a xylene petroleum resin mixed solution; the xylene petroleum resin solution is added to a bubble reactor, and then an ozone-oxygen mixture (O 3 -2% volume concentration) at 0.03s -1 The mixture was introduced into a reactor and reacted at 8°C for 50 minutes. After cooling, the xylene petroleum resin solution was mixed with monoethanolamine at a mass ratio of 84% and 16%, and then added into a glass reactor equipped with a reflux condenser and a stirring device, and reacted at 90°C for 2.5 hours to obtain a modified petroleum resin.
[0089] (2) An ultra-high molecular weight polyethylene with a weight average molecular weight of 10.2 million and a modified petroleum resin with a weight average molecular weight of 3000 were taken, and the above-mentioned composition was blended and melted in the mixing chamber of a Haake rheometer 300P, and then cooled to obtain an ultra-high molecular weight polyethylene modified composite material, with a rotor speed of 80 rpm, a temperature of 200°C, and a time of 20 min.
[0090] (3) HDPE is 90 parts by weight, and UHMWPE modified composite material is 10 parts by weight; based on 100 parts by weight of HDPE and UHMWPE, the components of nucleating agent and compatibilizer are mechanically mixed in a ratio of 0.4 parts by weight of barium sulfate, 0.6 parts by weight of calcium carbonate and 2 parts by weight of maleic anhydride, respectively, with a rotor speed of 4500 rpm, a feed rate of 3 kg / h, and a barrel temperature of 250°C;
[0091] The polyolefin composite material particles were subjected to a platen vulcanizing press to obtain a polyolefin composite material sheet at a temperature of 220° C., a pressure of 20 MPa, and a time of 20 min. The test results are shown in Table 1.
[0092] Example 10
[0093] This example prepares a low hydrogen permeability polyolefin composite material according to the method of Example 9, except that:
[0094] In step (3): based on 100 parts by weight of the HDPE and UHMWPE modified composite materials, the nucleating agent and the compatibilizer are mechanically mixed in a ratio of 0.3 parts by weight of barium sulfate, 0.5 parts by weight of calcium carbonate and 0.5 parts by weight of maleic anhydride respectively; the rotor speed is 4500 rpm, the feed rate is 3 g / min, the barrel temperature is 230°C, and the test results are shown in Table 1.
[0095] Embodiment 11
[0096] The method of Example 1 was followed except that calcium carbonate was replaced by an equal weight portion of SiO 2 .
[0097] Example 12
[0098] The method of Example 7 is followed, except that no compatibilizer is added.
[0099] The viscoelastic diagrams of the materials obtained in Examples 7 to 12 are shown in Figure 2 From Examples 7-9, it can be clearly seen that the ultra-high speed of the ultra-high-speed screw promotes crystallization; from Example 10, it can be seen that reducing the speed and temperature will reduce the crystallinity; from Examples 11-12, it can be seen that the synergistic promoting effect of calcium carbonate and barium sulfate nucleating agents, and the promoting effect of the compatibilizer on crystallization.
[0100] Comparative Example 1
[0101] The method of Example 7 is followed, except that: "the cooled xylene petroleum resin solution is mixed with monoethanolamine at a mass ratio of 94% and 6%" is replaced with "the cooled xylene petroleum resin solution is mixed with monoethanolamine at a mass ratio of 85% and 15%";
[0102] Other conditions are the same as in Example 7.
[0103] Comparative Example 2
[0104] The method of Example 7 is followed, except that no nucleating agent or compatibilizer is added; other conditions are the same as those of Example 7.
[0105] Comparative Example 3
[0106] The method of Example 7 was followed, except that monoethanolamine was not added; other conditions were the same as those of Example 7.
[0107] Comparative Example 4
[0108] The method of Example 9 was followed, except that monoethanolamine was replaced with an equal weight of triethanolamine.
[0109] Comparative Example 5
[0110] On the basis of Example 2, step (1) is omitted and the petroleum resin is not modified, and the petroleum resin is directly mixed with the ultra-high molecular weight polyethylene. The rest is the same as Example 2.
[0111] The viscoelastic diagrams of the materials obtained in Comparative Examples 1 to 5 are shown in Figure 3 Comparative Example 1 illustrates the nucleating agent, compatibilizer and the modification of petroleum resin to promote crystallization. In Comparative Example 4, triethanolamine is used instead, and the increase in hydroxyl groups promotes the fluidity of ultra-high PE, thereby promoting crystallization.
[0112] Table 1
[0113]
[0114] It can be seen from the results in Table 1 that the present invention improves the tensile strength value of the polyolefin composite material by combining the modified petroleum resin and ultra-high PE with specific component contents, that is, improves the elongation at break of the polyolefin composite material;
[0115] Through Examples 5-6 and Examples 7-9, it can be seen that modifying ultra-high PE by modifying petroleum resin helps to increase the fluidity of ultra-high PE and promote crystallization; at the same time, the speed of the ultra-high-speed screw is much higher than that of the traditional twin-screw, which can improve the fluidity of ultra-high PE in HDPE, thereby promoting crystallization;
[0116] It can be seen from Examples 1-3 that the hydrogen permeability value is lower, and the ultra-high PE modified composite material can better promote dispersion in HDPE, thereby promoting crystallization; it can be seen from Comparative Examples 3, 4, 11, 12 and the comparative examples that when monoethanolamine, nucleating agent and compatibilizer are not added, the hydrogen permeability is high, and it is difficult to obtain a polyolefin composite material with high hydrogen storage efficiency.
[0117] It can be seen from Comparative Example 5 that when the petroleum resin is not modified, the performance of the obtained composite material sheet is reduced. Modifying the petroleum resin by monoethanolamine and then modifying the ultra-high PE by modified petroleum resin can increase the fluidity of the ultra-high PE and improve the nucleation and crystallization ability of the ultra-high PE, which helps to further enhance the hydrogen storage effect and mechanical properties of the polyolefin composite material.
[0118] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a low hydrogen permeability polyolefin composite material, characterized in that: include, Mixing petroleum resin and xylene to prepare a xylene petroleum resin mixed solution; An oxidant is added to a xylene petroleum resin mixed solution to carry out an oxidation reaction, and after cooling, the solution is hydrothermally reacted with monoethanolamine to obtain a modified petroleum resin; The ultra-high molecular weight polyethylene and the modified petroleum resin are blended and melted, and then cooled to obtain an ultra-high molecular weight polyethylene modified composite material; The high-density polyethylene and ultra-high molecular weight polyethylene modified composite materials are mixed, a nucleating agent and a compatibilizer are added, and then mechanically mixed to obtain polyolefin composite material particles; The polyolefin composite material particles are passed through a flat vulcanizing press to obtain a low hydrogen permeability polyolefin composite material.
2. The preparation method according to claim 1, characterized in that: Calculated by the mass proportion of raw materials, the petroleum resin is 9 to 13 parts, and the xylene is 87 to 96 parts.
3. The preparation method according to claim 1 or 2, characterized in that: The oxidant is an oxygen-ozone mixture, wherein the volume concentration of O3 is 2%.
4. The preparation method according to claim 3, characterized in that: The oxidation reaction has a reaction temperature of 3 to 8° C. and a reaction time of 20 to 50 minutes.
5. The preparation method according to claim 4, characterized in that: The mass percentage of the monoethanol and the cooled xylene petroleum resin solution is 6-12%:88-94%; the hydrothermal reaction, wherein the reaction temperature is 70-90° C., and the reaction time is 1-3 hours.
6. The preparation method according to claim 1, characterized in that: The ultra-high molecular weight polyethylene and the modified petroleum resin are blended and melted, wherein the weight average molecular weight of the ultra-high molecular weight polyethylene is 3 million to 9 million, and the weight average molecular weight of the modified petroleum resin is 1000 to 2500; the blending and melting includes blending and melting in the mixing chamber of the Haake rheometer 300P, wherein the rotor speed is 50 to 70 rpm, the temperature is 150 to 170° C., and the time is 7 to 15 minutes.
7. The preparation method according to claim 1 or 6, characterized in that: Calculated by the weight of the raw materials, the ultra-high molecular weight polyethylene modified composite material is 10 to 50 parts by weight, the high-density polyethylene is 50 to 90 parts by weight, the content of the nucleating agent is 0.003 to 1 part by weight, and the content of the compatibilizer is 0.4 to 2 parts by weight; The weight average molecular weight of the high-density polyethylene is 120,000 to 300,000.
8. The preparation method according to claim 7, characterized in that: The mechanical mixing, wherein the mixed extrusion conditions include: a rotor speed of 2000 to 4500 rpm, a feed rate of 0.3 to 3 kg / h, and a barrel temperature of 200 to 250°C; The platen vulcanizing press platen pressing conditions include: temperature of 180-220° C., pressure of 10-20 MPa, and time of 5-20 min.
9. The low hydrogen permeability polyolefin composite material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The low hydrogen permeability polyolefin composite material has a tensile strength of 1.6 to 4.2 cN / dtex, an elongation at break of 30% to 62%, a modulus of 27 to 68 cN / dtex, and a hydrogen permeability of 1.56×10 -16 ~4.687×10 -16 mol / (m·s·Pa).
10. Use of the low hydrogen permeability polyolefin composite material according to claim 9 in the preparation of a hydrogen storage container.
Citation Information
Patent Citations
High-molecular-weight polymer nucleating agent-modified ultrahigh-molecular-weight polyethylene blend material
CN104004253A
Dense shish-kebab super-strong and super wear-resistant polyethylene composite material and preparation method thereof
CN109333897A
UHMWPE modified PE pipe special material
CN116874906A
Preparation method of HDPE / UHMWPE / YPnm alloy material
CN117024867A
High-temperature-resistant petroleum resin dispersion plugging agent and preparation method and application thereof
CN108531153A